A Comprehensive Profile Analysis of the Effect of Job Embeddedness on Turnover Intention among New Generation of Rural Migrant Workers in China: Based on PLS-SEM - Meirun, Tang; Sin, Jennie Soo Hooi; Wei, Chuah Chin (Advances in Social Sciences Research Journal, 2018)
This paper aimed to examine the relationship between organization embeddedness (OE), community embeddedness (CE) and turnover intention in the context of manufacturer sector in China. A 37-item questionnaire was filled by 384 new generation of rural migrant workers. Data were examined through a first-order of reflective model (SME1) and a two-stage of second-order reflective-formative hierarchical model (SME2) with the technical of Partial Least Squares. The empirical test results indicated that both OE and CE negative and significant related to turnover intention. When further disaggregated the components of OE and CE into the three sub-dimensions of fit, links, and sacrifice, this study found that causal indicator model of job embeddedness predict more variance of turnover intention than reflective model. Moreover, this study found that OEF, OES, CEF, and CES negative and significantly associated with turnover intention, while OEL positive related to turnover intention. Additionally, CEL did not show significant impact on turnover intention. The study concludes with several implications and recommendations for future research.